Coping, PTSD Symptoms and Alcohol Involvement in Trauma-Exposed College Students in the First Three Years of College - Read, Jennifer P. (Psychol Addict Behav, 2014)
The objective of the present study was to examine prospective, bidirectional associations among posttraumatic stress disorder (PTSD) symptoms, coping style, and alcohol involvement (use, consequences), in a sample of trauma-exposed students just entering college. We also sought to test the mechanistic role that coping may play in associations between PTSD symptoms and problem alcohol involvement over time. Participants (N=734) completed measures of trauma exposure, PTSD symptoms, coping, and alcohol use and consequences in September of their first college year (Y1) and again each September for the next two years (Y2–3). We observed reciprocal associations between PTSD and negative coping strategies. In our examination of a mediated pathway through coping, we found an indirect association from alcohol consequences and PTSD symptoms via negative coping, suggesting that alcohol consequences may exacerbate posttraumatic stress over time by promoting negative coping strategies. Trauma characteristics such as type (interpersonal vs. non-interpersonal) and trauma re-exposure did not moderate these pathways. Models also were invariant across gender. Findings from the present study point to risk that is conferred by both PTSD and alcohol consequences for using negative coping approaches, and through this, for posttraumatic stress. Interventions designed to decrease negative coping may help to offset this risk, leading to more positive outcomes for those students who enter college with trauma exposure.